Motivation Modulates Visual Attention: Evidence from Pupillometry - Wykowska, Agnieszka; Anderl, Christine; Schubö, Anna; Hommel, Bernhard (Frontiers in Psychology, 2013)
Increasing evidence suggests that action planning does not only affect the preparation and execution of overt actions but also “works back” to tune the perceptual system towards action-relevant information. We investigated whether the amount of this impact of action planning on perceptual selection varies as a function of motivation for action, which was assessed online by means of pupillometry (Experiment 1) and visual analogue scales (VAS, Experiment 2). Findings replicate the earlier observation that searching for size-defined targets is more efficient in the context of grasping than in the context of pointing movements (Wykowska, Schubö, & Hommel, 2009). As expected, changes in tonic pupil size (reflecting changes in effort and motivation) across the sessions, as well as changes in motivation-related scores on the VAS were found to correlate with changes in the size of the action-perception congruency effect. We conclude that motivation and effort might play a crucial role in how much participants prepare for an action and activate action codes. The degree of activation of action codes in turn influence the observed action-related biases on perception.